Delegation and Dynamic Incentives - Dongsoo Shin; Roland Strausz (Center for Economic Studies and ifo Institute (CESifo), 2014)
Using an agency model, we show how delegation, by generating additional private information, improves dynamic incentives under limited commitment. It circumvents ratchet effects and facilitates the revelation of persistent private information through two effects: a play-hardball effect, which mitigates an efficient agent's ratchet incentive, and a carrot effect which reduces an inefficient agent's take-the-money-and-run incentive. Although delegation entails a loss of control, it is optimal when uncertainty about operational efficiency is large. Moreover, delegation is more effective with production complementarity. We also consider different modes of commitment to yield insights into optimal organizational boundaries.
Keywords: D82; D86; L22; 330; agency; delegation; dynamic incentives; limited commitment